A Review on Phytochemical & Pharmacological Profile of Pergularia Daemia linn. - Chandak, Raman R; Dighe, Nachiket S (Journal of Drug Delivery and Therapeutics, 2019)
Many indigenous Indian medicinal plants have been found to be successfully used to manage diabetes and some of them have been tested and active principles isolated. However, search for new antidiabetic drugs for effective treatment is on. The vast majority of people on this planet still rely on their traditional material medica (medicinal plants and other materials) for their everyday health care needs. It is also a fact that one quarter of all medical prescriptions are formulations based on substances derived from plants or plant-derived synthetic analogs. The herbal drug from tribal region is selected for the study which is used for diabetes andliver diseases. Pergularia daemia (Asclepiadaceae) is a perennial herb growing widely along the road sides of India. It has been used in folk medicine for the treatment of Dibetis mellitus &liver disorders. It is widely distributed in the tropical and sub tropicalregions of the world. Various phytochemical including terpenoid, flavonoids, sterols and cardenolids have been isolated andidentified from the various parts of the plant (leaves, stems, shoots, roots, seeds and fruits whole plant). P. daemia widely used by various tribal communities in Western Ghats of India for the treatment of variety of ailments, while predominantly the roots of theplant have been used to treat liver disease and jaundice.The present review article aims towards medicinal Pharmacological potential, Bioactive remedies, Phytochemical profile and other important aspects of P. daemia.Keywords: Ethnobotanical uses, Pergularia daemia, Pharmacological Profile, Phytochemical Profile